Neuromotor Compromise as a Presenting Symptom in Advanced Lower Extremity Soft Tissue Sarcoma: A Case Series - Adam Maestas; Parsa Charkhchi; Farbod Malek (HCA Healthcare Journal of Medicine, 2026)
Background Soft tissue sarcomas (STS) are rare malignant tumors of mesenchymal origin, representing less than 1% of adult cancers. Approximately half arise in the extremities, most often presenting as a painless, enlarging mass. Symptoms are often misattributed to benign neuropathic or musculoskeletal causes, leading to delayed diagnosis and treatment. Neurological deficits such as foot drop or distal weakness are exceptionally uncommon presenting signs and generally indicate advanced local invasion or compression of major peripheral nerves. Recognizing acute neuromotor compromise as a potential manifestation of soft tissue malignancy is crucial for timely oncologic evaluation and limb-sparing management. Case Presentation This series describes 3 patients who presented with acute or progressive foot drop as the initial symptom of advanced lower extremity STS. Case 1: A 27-year-old man presented with an 8-month history of progressive right foot drop and sensory loss. Magnetic resonance imaging (MRI) revealed a 6.4-cm popliteal fossa tumor encasing the common peroneal nerve, consistent with a malignant peripheral nerve sheath tumor (MPNST). He received neoadjuvant chemoradiation followed by en bloc resection with negative margins and retained independent ambulation using an orthosis. Case 2: A 15-year-old girl developed right foot drop and swelling of the thigh and knee. Magnetic resonance imaging demonstrated a 32-cm posterior thigh mass encasing the sciatic nerve. Biopsy confirmed Capicua transcriptional repressor (CIC)-rearranged undifferentiated round cell sarcoma. She underwent multimodal therapy, including neoadjuvant chemotherapy, nerve-sacrificing resection, and adjuvant radiotherapy, remaining in remission at 12 months. Case 3: A 43-year-old woman with prior myxoid liposarcoma presented with recurrent left thigh pain and new foot drop. Imaging revealed a 12-cm ischiofemoral mass compressing the sciatic nerve. Wide excision with nerve sacrifice achieved clear margins, and adjuvant chemotherapy was completed. At 12 months, she remained disease-free and ambulatory with an ankle-foot orthosis (AFO). Conclusion New-onset foot drop should raise suspicion for an underlying STS, particularly when symptoms are progressive or unresponsive to conservative management. Awareness of neuromotor compromise as a potential red-flag symptom may reduce diagnostic delay, facilitating earlier referral, multidisciplinary intervention, and improved functional outcomes. The involved nerves were sacrificed during surgery in all of our cases.